Preparation and Characterization of Epoxidised and Acrylated Styrene/Isoprene/Styrene (SIS) Triblock Block Copolymer Based Nanocomposites - Khanal, Santosh; Shakya, Alina; Michler, Goerg H.; Youssef, Boulos; Saiter, Jean M.; Adhikari, Rameshwar (Journal of Nepal Chemical Society, 2013)
In this work, a commercially available Styrene-Isoprene-Styrene (SIS)triblock copolymer was modified into epoxidised version (ESIS)using performic acid generated in situ from hydrogen peroxide and formic acid. The epoxidised sample was further acrylated to prepare acrylated version (ASIS). The nanocomposites of each sample (SIS, ESIS and ASIS) were prepared using boehmite nanoparticles as filler by solution casting method. The polymers were characterized by Fourier Transform Infrared (FTIR) spectroscopy and transmission electron microscopy (TEM). TEM investigations revealed that that the epoxidation of the diene block enhanced the dispersion of the nanofiller in the polymer matrix while the segregation of the nanoparticles towards the interface of the immiscible polymers was observed in the acrylated block copolymer based nanocomposite. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8112 Journal of Nepal Chemical Society Vol. 28, 2011 Page: 84-88 Uploaded Date: May 24, 2013